2018
DOI: 10.1111/fog.12387
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental conditions on the reproductive success and recruitment of the Argentine hake Merluccius hubbsi (southwestern Atlantic Ocean)

Abstract: The Argentine hake Merluccius hubbsi represents the dominant demersal fish and one of the main fisheries in the Argentine Sea. We analyzed over 17 years (September 1997–February 2015) of satellite surface chlorophyll concentration (CHL) and sea surface temperature anomaly (SSTA) data in the main spawning (SUB) and nursery (SJG) areas of the Patagonian stock of M. hubbsi. The variability observed in these environmental conditions was related to interannual differences in the reproductive success of hake. CHL va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
2
8
1
Order By: Relevance
“…In agreement with our results, Marrari et al. (2019) suggested that the years with higher egg production lead to high densities of early developmental stages and consequently to higher density‐dependent mechanisms reducing the survival of juveniles and later recruitment to the adult stage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our results, Marrari et al. (2019) suggested that the years with higher egg production lead to high densities of early developmental stages and consequently to higher density‐dependent mechanisms reducing the survival of juveniles and later recruitment to the adult stage.…”
Section: Discussionsupporting
confidence: 93%
“…Such densities of prey present in the stratified zone would allow greater efficiency in larval feeding since the energy costs associated with food search would be reduced. Supporting our results, Marrari, Macchi, Santos, and Leonarduzzi (2019) observed that the most favorable conditions for M. hubbsi recruitment and its larval survival were cold temperatures (colder than average fall temperatures) in combination with high spring chlorophyll concentrations. They suggested that the higher survival associated with colder seasons might be the result of less competition for food between hake larvae and other plankton predators.…”
Section: Discussionsupporting
confidence: 89%
“…Linear model relating the mean temperature of the catch (MTC) with the sea surface temperature anomaly (SSTA) and the fishing fleet diversity (Simpson index). **p < 0.01 more, recent reports from a nearby region concluded that the reproductive success indexes of Argentine hake were negatively correlated with SST, particularly in autumn (late larval or early juvenile phase; Marrari et al 2019). In contrast, the wide thermal niche of whitemouth croaker and its affinity for warm waters mean that this species may be less sensitive to an increase in regional SST.…”
Section: Discussionmentioning
confidence: 90%
“…Phytoplankton phenology is known to be strongly impacted by meteorological variables, particularly wind and solar irradiance. The timing of spring and autumn phytoplankton blooms have consequences that cascade through the food web (Edwards & Richardson, 2004) and have been shown to affect fish stocks and spawning, copepod reproduction and shrimp survival (Kodama et al, 2018;Leaf & Friedland, 2014;Marrari et al, 2019;Platt et al, 2003;Richards et al, 2016). If high-resolution meteorological data is not available, the ability of hydrodynamic-ecosystem models to capture the impact of short-term fluctuations in wind stress, light availability and other key meteorological variables on bloom phenology and carbon cycling is limited.…”
Section: Discussionmentioning
confidence: 99%